Relationships between playing time and selected NBA Combine Test performance in Division I Mid-Major basketball players - Lockie, R. G.; Beljic, A.; Ducheny, S.; Kammerer, J.; Dawes, J. J. (International Journal of Exercise Science, 2020)
There has been limited analyses of DI mid-major male basketball players, and no analyses of relationships between athletic abilities and playing time in this population. The purpose of this study was to (1) describe and compare backcourt and frontcourt players from one mid-major team and (2) determine if there were relationships between playing time (total minutes, total games played, minutes per game) and select tests from the NBA Combine (height, body mass, standing reach, and wingspan; countermovement [VJ] and approach [AppVJ vertical jump], lane agility drill, ¾ court sprint, and 83.91-kg bench press). A retrospective analysis of data from the 2018 season for a men`s DI team (n = 10) was conducted. Performance testing was completed in the pre-season, and playing time metrics were collated by the team`s staff over the season. Players were split into backcourt (n = 6) and frontcourt (n = 4) groups and compared via independent samples t-tests (p < 0.05) and effect sizes (d). Pearson`s correlations calculated relationships between playing time metrics and the NBA combine test data (p < 0.05). When compared to the backcourt group, the frontcourt group were significantly taller, heavier, had a greater standing reach and wingspan, and performed poorer in the VJ, AppVJ, and ¾ court sprint (d = 1.49-3.45). There were no significant relationships between playing time and any NBA Combine test (r = -0.363-0.511). Basketball-specific skill may have a larger impact on playing time in this mid-major team. However, the mid-major players in this study may have had above-average athletic abilities as measured by NBA combine testing, limiting correlations with playing time.